Intestinal inflammation alters mucosal carbohydrate foraging and monosaccharide incorporation into microbial glycans. (6th October 2020) - Weiss, Gisela Adrienne; Grabinger, Thomas; Glaus Garzon, Jesus; Hasler, Tobias; Greppi, Anna; Lacroix, Christophe; Khanzhin, Nikolay; Hennet, Thierry
Abstract: Endogenous carbohydrates released from the intestinal mucus represent a constant source of nutrients to the intestinal microbiota. Mucus‐derived carbohydrates can also be used as building blocks in the biosynthesis of bacterial cell wall components, thereby influencing host mucosal immunity. To assess the uptake of endogenous carbohydrates by gut microbes in healthy mice and during intestinal inflammation, we applied azido‐monosaccharides that can be tracked on bacterial cell walls after conjugation with fluorophores. In interleukin‐10 deficient mice, changes in the gut microbiota were accompanied by decreased carbohydrate hydrolase activities and increased lumenal concentrations of host glycan‐derived monosaccharides. Tracking of the monosaccharide N ‐azidoacetylglucosamine (GlcNAz) in caecum bacteria revealed a preferential incorporation of this carbohydrate by Xanthomonadaceae in healthy mice and by Bacteroidaceae in interleukin‐10 deficient mice. These GlcNAz‐positive Bacteroidaceae fractions mainly belonged to the species B. acidifaciens and B. vulgatus . Growth of Bacteroides species in the presence of specific monosaccharides changed their stimulatory activity toward CD11c + dendritic cells. Expression of activation markers and cytokine production was highest after stimulation of dendritic cells with B. vulgatus . The variable incorporation of monosaccharides by related Bacteroides species underline the necessity to investigate intestinal bacteria down to the species level when addressing microbiota‐host interactions.